Agryppa, Marcellus i pierścień Augusta. Kilka uwag na temat fragmentu Historii rzymskiej Kasjusza Diona (53, 30, 1–2) - Sawiński, Paweł (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
In the article I make an interpretation of one of the fragments of The Roman History by Cassius Dio, refering to Augustus` illness in 23. I am trying to answer a question how the fact of handing over a personal ring to Agrippa by Augustus should be understood and, more than that, whether we can perceive Marcellus, emperor`s nephew and son-in-law as his planned successor. I am also touching the problem of the alleged rivalry between Agrippa and Marcellus, which was mentioned by ancient authors.
Agrippa, Marcellus and the Ring of Augustus. Some comments on the Fragment of Roman History of Cassius Dio
In the article I am making an attempt to interpret one of the extracts of The Roman History by Cassius Dio in which the author gives us a relation of a meeting of Augustus with the most important magistrates, senators and knights at the time of princeps’ serious disease, which he started to suffer from in 23 BC. What I am basically trying to do is to set up how we should understand handing over Augustus’ personal ring to Agrippa. I do not agree with existing interpretations which assume that giving the ring to Agrippa was related to his appointing to be a political successor or a private heir to the princeps. In my opinion Augustus wanted his long standing friend and associate just to tidy his private matters in case of death, at the same time appointing him to execute his final will. Another problem that appears in the context of the analysis of the upper extract is a question of planned succession of Marcellus, princeps nephew and son-in-law. Relying mainly on the testimony of numismatic and iconographic sources I challenge a picture of Marcellus as a planned successor to Augustus, which has become established in ancient literature. Moreover, Augustus` actions show that we do not have any significant tips to think that princeps was creating his son-in-law to become his political successor. The last question I discuss is a problem of alleged rivalry between Agrippa and Marcellus, which was mentioned by a few ancient historians. The conflict was believed to finally lead to Agrippa leaving Rome for the East. However, accepting such a version arouses serious doubts. Most of our authors suggesting the existence of an open conflict between Agrippa and Marcellus were the most probably inspired by the later rivalry of Tiberius with young Caesars, which was finally to make Augustus’ stepson remove from political life and go away to Rhodes in 6 BC. From that perspective they also perceived Agrippa`s earlier going to the East. Relying on Josephus Flavius`s words we might however assume that Agrippa`s journey to the East was mainly aimed at ordering a few things in the region (a Parthian question, Rome`s relation with the rulers of vassal kingdoms, control of the administration system in provinces).
Keywords: Cassius Dio; political successor; Augustus; Agrippa; Marcellus; signet ring of Augustus